Analysis Technique on Water Permeability in Concrete with Cold Joint considering Micro Pore Structure and Mineral Admixture. (20th August 2015) - Choi, Se-Jin; Kang, Suk-Pyo; Kim, Sang-Chel; Kwon, Seung-Jun
Abstract : Cold joint in concrete due to delayed concrete placing may cause a reduced shear resistance and increased water permeation. This study presents an analytical model based on the concept of REV (Representative Element Volume) to assess the effect of water permeability in cold joint concrete. Here, OPC (Ordinary Portland Cement) concrete samples with cold joint are prepared and WPT (Water Permeability Test) is performed on the samples cured for 91 days. In order to account for the effect of GGBFS (Granulated Ground Blast Furnace Slag) on water permeability, concrete samples with the same W/B (Water to Binder) ratio and 40% replacement ratio of GGBFS are tested as well. Utilizing the previous models handling porosity and saturation, the analysis technique for equivalent water permeability with effective cold joint width is proposed. Water permeability in cold joint increases to 140.7% in control case but it decreases to 120.7% through GGBFS replacement. Simulation results agree reasonably well with experimental data gathered for sound and cold joint concrete.